Sleep disorders among children attending the paediatric clinic in Universiti Sains Malaysia (USM) Hospital - Nazzlin Dizana, Din (2008)
To evaluate the frequency of sleep disorders among children attending the pediatric clinic in USM Hospital The Sleep Disturbance Scale for Children (SDSC) consisting of 26 items which concentrates on six sleep disorders, Disorder of Initiating and Maintaining Sleep (DIMS), Sleep Breathing Disorder (SBD), Sleep Wake Transition Disorder (SWTD), Sleep Hyperhydrosis (SHY), Disorder of Arousal (DA), Disorder of Excessive Somnolence (DOES), was translated to Bahasa Malaysia. Parents of chi ldren aged 4-16 years attending the paediatric clinic, USM Hospital from December 2005 to February 2008 were requested to complete the SDSC while awaiting consultation Among 684 children from 8 sub-specialty clinics who completed the SDSC, there were 361 (52.8%) boys. The number(%) of children in each age group was as follows: 6-12 years old (462, 67.5%), 4-5 years old (86, 12.6%), more than 12 years old (136, 19.9%). Sixty-three (9.2%; 95% Cl 7.3% to 11.6%) children had a significant total sleep problem score. The proportion of children with specific sleep disorders were as follows: 64 (9.4%) DIMS, 55 (8.0%) SBD, 31 (4.5%) SWTD, 27 (3.9%) SHY, 31 (4.5%) DA, and 57 (8.3%) DOES. Regression analysis revealed that the frequency of SBD (p=0.01) and SWTD (p=0.03) was significantly different among subspecialty clinics, and children aged more than12 years had a significantly higher prevalence of DOES (p=0.03) than other age groups. No significant gender differences were observed Sleep disorders were relatively high among children attending the paediatric clinic in USM Hospital. Given the impact of sleep disorders on children and families, there is a need for increased awareness of children 's sleep problems in the clinics and community.